IMPLEMENTATION OF DEEP LEARNING, LEARNING ENGAGEMENT, AND EMOTIONAL REGULATION ON THE IMPROVEMENT OF CRITICAL THINKING AND COLLABORATION AMONG ELEMENTARY SCHOOL STUDENTS : english - Riska Novianty; Yeni Yuniarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Contemporary education faces substantial challenges in preparing elementary students for twenty-first century competencies, necessitating transformative pedagogical approaches beyond conventional instruction. This quasi-experimental investigation examined the influence of deep learning pedagogy on critical thinking abilities and collaborative competencies among fifth-grade elementary students, by student engagement and emotional regulation hypothesized as mediating mechanisms. Forty participants were systematically allocated into experimental and control cohorts, receiving deep learning intervention and conventional instruction respectively across an eight-week duration. Quantitative analysis utilizing ANCOVA revealed statistically significant enhancement in critical thinking (F = 58.743, p < 0.001, partial η² = 0.614) and collaboration (F = 52.186, p < 0.001, partial η² = 0.586) inside of the experimental cohort. Path analysis confirmed partial mediation effects, by student engagement mediating 42.8% of critical thinking variance and 40.3% of collaboration variance, while emotional regulation mediated 29.9% and 31.2% respectively. Structural equation modeling demonstrated acceptable model fit (CFI = 0.942, RMSEA = 0.068), explaining 71.3% of critical thinking variance and 68.7% of collaboration variance. Qualitative observations documented progressive transformation in classroom discourse patterns, collaborative behaviors, and metacognitive awareness. Findings provide empirical substantiation for deep learning implementation in elementary contexts, highlighting interconnected roles of behavioral participation, emotional investment, cognitive strategy deployment, and affective regulation in fostering higher-order thinking and interpersonal competencies essential for future-ready learners. This is an open access article under the CC–BY-SA license.